First Cretaceous (Albian) invertebrate fossil assemblage from Batavia Knoll, Perth Abyssal Plain, eastern Indian Ocean: taxonomy and paleoecological significance. (14th September 2016) - Wild, Toban J.; Stilwell, Jeffrey D.
Abstract: The first sedimentary rocks from Batavia Knoll, on the western edge of the Perth Abyssal Plain, eastern Indian Ocean, have been recovered, yielding an assemblage of invertebrate fossils hitherto undocumented from this part of the world. The fauna consists of 22 species of Mollusca, including new gastropods, a calliotropid Planolateralus acanthanodus n. sp.; a margaritid Igonoia levimargarita n. sp.; a procerithiid Procerithium arenacollicola n. sp.; and aporrhaids Drepanocheilus bataviensis n. sp. and Anchura pelsaerti n. sp. In addition, pleurotomariid, ringiculid, and architectonicid gastropod taxa were recovered. Bivalves are represented by members of the Nuculanidae, Inoceramidae, Pinnidae, Buchiidae, Lucinidae, Veneridae, and Hiatellidae. Scaphopods (Dentaliidae) and ammonites (two taxa, of Desmoceratidae and Hamitidae) are also present. Further recovered were one species of Serpulidae (Polychaeta), two of Trachyleberididae (Ostracoda), and a probable echinoid fragment. The fossil assemblage was dominated by shallow marine suspension-feeding taxa (39% of the suite). Detritivorous and herbivorous taxa comprised 22% and 9%, respectively, with nektic and epifaunal carnivores amounting to 30%. Taphonomic analyses of these fossils and their host sedimentary facies revealed the Batavia Knoll sandstone was deposited in a shallow marine environment during a mass-flow event. Biostratigraphic range data of the preserved macro- and microfossil assemblages imply an age of latest Albian, contemporaneous with the rifting of Batavia Knoll from Greater India during the broader India–Australia–Antarctica breakup in the mid-Cretaceous.